Diurnal Variations and Frequency Distribution of Air Pollutants Concentration in, Kuala Lumpur and its Outskirts - A Preliminary Analysis - Inouye, Rikita; Zainal Abidin, Azman (1986)
Three continuous air monitoring stations were each installed in Kuala Lumpur, Serdang and Kajang. A preliminary analysis on the diurnal variations and frequency distribution of the pollutants concentration was made, using data obtained from 10th. April - 5th. May 1985. The diurnal variations for the primary pollutants showed two distinct peaks in Kuala Lumpur. These peaks were, however, not clearly defined at the other sites. Secondary pollutants, on the other hand exhibited 'normal' diurnal variations at all' the sites. A frequency distribution analysis was also carried out to give a clearer comparison of the pollutants concentration, among the sites.